The Structure of the Share Capital and the Interests of the Majority Shareholder - Shadova, Zalina H.; Gurianov, Pavel A.; Fedorova, Svetlana N.; Zemlyakova, Alina V.; Grishchenko, Olga V. (International Journal of Economics and Financial Issues, 2016)
Smoothing the contradictions between shareholders and managers - the main task of the members of the Board of Directors. That is why the Board of Directors lays down the task of developing a system of prevention and settlement of corporate conflicts. However, it should be noted that in order to solve this problem, the board should not be formal, but actually separated and independent from both the shareholders and managers of. The most “conflict” in the field of corporate law is the relationship, which is on the different interests of different stakeholders. Federal Law “On Joint Stock Companies” sets a sufficiently rigid canvas, within which can be built into the control system of a particular company. Based on this essential element of the concept of corporate legislation should be to identify the vectors improving the management model proposed by the Federal Law “On Joint Stock Companies” (Legislative Assembly 1996, Legislative Assembly 1995). Such analysis should be conducted for, firstly, the body of each company, and secondly, the distribution of competence between all bodies. Only such an analysis is twofold will create legal prerequisites for the creation of effective interaction of organ systems in Russian companies. Keywords: capital structure, majority shareholder, retail, conflict of interest JEL Classifications: D74, H70, K20